Needs of Parents in Caring for Their Children in a Pediatric Intensive Care Unit - Valderrama Sanabria, Mery Luz; Muñoz de Rodríguez, Lucy (Investigación y Educación en Enfermería, 2016)
Objective. This work sought to describe the needs of parents to participate in caring for their children hospitalized in a pediatric intensive care unit (PICU). Methods. This is a qualitative study based on the ethno-nursing research method proposed by Leininger. For data collection and analysis, in-depth open interviews were used, along with field notes and enabler guidelines proposed by Leininger: stranger-friend, observation, participation, reflexion, and the Sunrise model. Parents of children hospitalized in a PICU in the city of Tunja (Boyacá, Colombia) participated between February 2012 and October 2013. Results. The needs of parents to care for their children were described in the following themes: clear and timely communication, familiarization with technology, the value of the family, favoring the parent-children interaction during visits, and valuing and respecting generic (folk) knowledge. Conclusion. The study provides knowledge, from the cultural perspective of parents with children hospitalized in PICU, as input to plan and develop care actions with them, according to their own needs. How to cite this article: Valderrama ML, Muñoz L. Needs of parents in caring for their children in a Pediatric Intensive Care Unit. Invest Educ Enferm. 2016; 34(1): 29-37